ANALISIS PENGEMBANGAN STRATEGI PEMASARAN HALAL PADA USAHA KECIL MENENGAH PRODUK WEDANG UWUH DAN TEPUNG BEBAS GLUTEN DI UKM PROGRESS JOGJA - Vembri Noor Helia (Teknoin, 2016)
The government is encouraging small businesses to improve product quality by adjusting its product in accordance with the Standar Nasional Indonesia (SNI-Indonesian National Standardization). Halal is one aspect of quality, especially in the food and beverage products, which is considered in Indonesia, due to most of Indonesian is Moslem. This research was aimed to develop halal marketing strategies for specific SME (Small Medium Enterprise) that produced â€œwedang uwuhâ€ beverage and gluten-free flour in Yogyakarta. The SME is called SMEs Progress Jogja. The marketing strategy in SMEs Progress Jogja was developed using a questionnaire that distributed to stakeholders. The tools which for analysis were SWOT matrix and QSPM. There are three expected strategies by the SMEs Progress Jogja that should be selected. The strategies were expanding the market share (especially by exploiting the defense of government), developing/increasing product variation, and also preserving the quality and the halal requirement of products. Then, the chosen strategy that was selected by using the priority matrix QSP is to expand market share.